A SCHEDULE OF CLEANING PROCESSES FOR A SINGLE-ARMED CLUSTER TOOL - Noh, Seung-Min; Kim, Ja-Hee; Jang, Seong-Yong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
Cluster tools have widely spread throughout most semiconductor fabrication processes over the decades. A conventional robot sequence of a single-armed cluster tool pursues a backward strategy for efficiency. However, we cannot guarantee that the strategy is optimal under some abnormal situations, such as breakdowns, and during auto-cleaning, also known as periodic cleaning for preventive maintenance. In this paper, we focus on auto-cleaning, which is undesirable but predictable. For auto-cleaning, we suggest alternative cleaning frequencies for time efficiency of a single-armed cluster tool that periodically cleans the inside of process modules. Additionally, we derive its heuristic robot scheduling from Petri-net models. Finally, we examine the effectiveness of our suggestions by simulation.